PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KEADILAN ORGANISASI TERHADAP KOMITMEN KERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN KERINCI: EDWAR, ST - EDWAR (JURNAL ADMINISTRASI NUSANTARA, 2021)
This study aims to determine the effect of independent variables on the dependent variable. The object of this research is the Kerinci Regency Education Office Staff. The number of samples in this study were 68 respondents. The analysis technique used is multiple linear regression. The results obtained by the partial test (t test) obtained: (a) There is a positive and significant influence of work motivation on work commitment. (b) There is a positive and significant influence of job satisfaction on work commitment. c) There is a positive and significant effect of organizational justice on work commitments. The results of the study simultaneously showed that work motivation, job satisfaction and organizational justice had a positive and significant effect on work commitment. work and organizational justice on the Work commitment dependent variable of 0,700 or 70.0%. While the remaining 30.0% is influenced by other variables outside this study.